2016
DOI: 10.1007/s00281-016-0562-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of mast cell and basophil lineage commitment

Abstract: Basophils and mast cells have long been known to play critical roles in allergic disease and in immunity against parasitic infection. Accumulated evidence supports that basophils and mast cells also have important roles in immune regulations, host defense against bacteria and viruses, and autoimmune diseases. However, origin and molecular regulation of basophil and mast cell differentiation remain incompletely understood. In this review, we focus on recent advances in the understanding of origin and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 84 publications
1
33
0
Order By: Relevance
“…GMP then led to classical monocytes that further led to myeloid dendritic cells on one branch and to cells labeled as intermediate monocytes on another branch. UMAP linked basophils to a population of Lin − cKit + Sca1 − CD34 + FcγRII/III + FcεRIα + cells, consistently with a previously-described phenotype for committed basophil progenitors [10]. These putative progenitors appeared closer to CMP than GMP, a topic that is still intensely debated.…”
Section: Umap Better Represents the Multi-branched Trajectory Of Hemasupporting
confidence: 79%
“…GMP then led to classical monocytes that further led to myeloid dendritic cells on one branch and to cells labeled as intermediate monocytes on another branch. UMAP linked basophils to a population of Lin − cKit + Sca1 − CD34 + FcγRII/III + FcεRIα + cells, consistently with a previously-described phenotype for committed basophil progenitors [10]. These putative progenitors appeared closer to CMP than GMP, a topic that is still intensely debated.…”
Section: Umap Better Represents the Multi-branched Trajectory Of Hemasupporting
confidence: 79%
“…However, the developmental relationship between basophils, mast cells, and other hematopoietic cells remains to be fully elucidated. 1 Several studies suggest that human basophils develop from common basophil-eosinophil progenitors (Fig 1). 2,3 Hybridtype cells possessing both basophil and eosinophil phenotypes have been detected in the bone marrow, cord blood, and peripheral blood of patients with myeloid leukemia.…”
Section: Ontogeny Of Basophilsmentioning
confidence: 99%
“…4,5 In mice multiple differential pathways that give rise to basophils might exist (Fig 1). 1 A recent study identified a novel population of common basophil-mast cell progenitors in mouse bone marrow. 6 A series of transcription factors are involved in the differentiation and commitment of basophils and mast cells.…”
Section: Ontogeny Of Basophilsmentioning
confidence: 99%
“…[1][2][3] It is now well accepted that basophils and mast cells are distinct cell lineages. 4 Recent studies have identified crucial roles for basophils, distinct from those played by mast cells, in immune responses including allergy and protective immunity. [5][6][7][8] In response to various stimuli, basophils can readily secrete large quantities of the cytokine interleukin-4 (IL-4), which plays a versatile role in immunity through regulating other cells.…”
Section: Introductionmentioning
confidence: 99%